Educational Robotics and Block-Based Programming: Teacher Education in Brusque/SC - Silva, Fabiana Coronel Da; Vicentini, Taiani; Mayer, Franciele Márcia; Groh, Ivanete Lago (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2025)
This article presents the experience of the Itinerant Educational Robotics Laboratory Project (LIRE) in the public school system of Brusque, Santa Catarina, Brazil. The initiative aims to democratize access to educational robotics and digital culture through the continuous training of teachers and monitors. The project promotes the use of block-based programming platforms-such as Scratch, Mblock, and Tinkercad-as accessible and intuitive tools for developing pedagogical practices aligned with the Base Nacional Comum Curricular and active methodologies. The results show increased engagement and autonomy among educators, interdisciplinary teaching practices, and significant student involvement in robotics clubs. Challenges such as infrastructure limitations and initial teacher resistance were addressed through methodological strategies focused on hands-on learning and collective experimentation.